Implementasi Multimedia Interaktif untuk Meningkatkan Literasi Digital dan Kemampuan Membaca Siswa Sekolah Dasar Dalam Pembelajaran Bahasa Indonesia - Fifi Lesley F. Pogoh; Ketut Agustini; I Gde Wawan Sudatha (Jayapangus Press, 2026)
Digital literacy and reading proficiency are critical 21st-century skills, yet Indonesian elementary students still struggle to meet international standards. This study aims to systematically identify the forms, effectiveness, and implementation challenges of interactive multimedia in Indonesian language learning. Using the Systematic Literature Review (SLR) method guided by PRISMA, 15 high-quality articles (2020–2025) were analyzed. The novelty of this study lies in its integrative synthesis that maps the evolution of media from static tools to dynamic ecosystems (gamified platforms, multimodal e-modules, and AR) aligned with the national Merdeka Curriculum. Findings indicate that these platforms significantly improve reading comprehension and digital literacy (p < 0.05) by optimizing cognitive load based on the Cognitive Theory of Multimedia Learning (CTML). In conclusion, technological effectiveness is not independent but moderated by the TPACK framework and teacher readiness as instructional designers. These results provide a conceptual framework for educators to integrate adaptive technology with responsive pedagogy for long-term literacy improvement.